Pengaruh Jumlah Objek Wisata dan Jumlah Hotel Terhadap Pendapatan Asli Daerah (PAD) di Kabupaten/Kota Provinsi Sumatera Barat - Fildzah Alyani; Menik Kurnia Siwi (Jurnal Ecogen, 2020)
This research aims to analyze influence of tourism place site and hotel toward Original Local Government Revenue (PAD) in West Sumatera Province Object of this research are West Sumatera Province Cities/Regencies. This research use Panel Least Square method to see the effect of independent variable toward dependent variable which took from West Sumatera Province Cities/Regencies from 2013 until 2017 data that are collected through documentation from local government institution. This research applies Random Effect Model (REM) approach. Result of this research shows that (1) Total amount of tourism place and hotels together has positive and significant influence towards Original Local Govenment Revenue (PAD) in West Sumatera Province Cities/Regencies. (2) Total amount of tourism place has not any significant influence towards Original Local Govenment Revenue (PAD) in West Sumatera Province Cities/Regencies. (3) Total amount of hotels has significant influence towards Original Local Govenment Revenue (PAD) in West Sumatera Province Cities/Regencies. From this research it is suggested for government to increase fund allocation as well permits thus can improve total amount of tourism place and hotels growth therefore can increase Original Local Govenment Revenue (PAD) in West Sumatera Province Cities/Regencies.Keywords : tourism place, hotels, original local govenment revenue (pad)